Faktor yang mempengaruhi respons petani terhadap program desa pertanian organik (DPO) empon-empon di Kecamatan Jumantono Kabupaten Karanganyar - Pipiet Endwiyatni; Suminah; Eksa Rusdiyana (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: Farmers' responses can be seen from four components, namely cognitive, affective, conative, and behavioral. This study aims to analyze the factors that influence farmers' responses to the Organic Farming Village program. Methods: The study used a quantitative approach with survey methods in Jumantono District, Karanganyar Regency. The population is all farmers who are members of the two farmer groups that the program applies to as many as 141 farmers. A sample of 60 farmers was taken using the Slovin formula. Data analysis used multiple linear regression analysis to measure the effect of factor X (non-formal education, experience, land area, sacrifices incurred, and the presence of field guides) on factor Y (Response). Results: The results of the analysis show that 83.3% of respondent farmers are in a good category. The equation from the analysis of multiple linear regression coefficients is Y = 79.147+ 2.415X1 + 2.113X2 + 10.443X3 + (-0.892)X4 + 4.811X5 with an R2 value of 0.667, which means that the X variable can explain the Y variable by 66.7%. The results of the F test are that all of the X variables simultaneously have a significant effect on the Y variable (significance level = 0.05). The results of the t-test showed that the variables of non-formal education, land area, and field guides had a significant effect on the response. Conclusion: Simultaneously, all variables significantly affect farmers' responses to the empon-empon DPO program.